Construction of a model of endometritis in domestic rabbits using equine-derived pathogens and evaluation of therapeutic effect of sensitive drugs - Ding, Xuanpan; Cui, Xiao; Shi, Jinlian; Cheng, Xiaoli; Yao, Dan; Gao, Yujin; Zhang, Yong (Frontiers in Veterinary Science, 2023)
The pathogenic bacteria were isolated from the uterine lavage fluid of a mare suffering from endometritis. Followed identified and purified, injected into the uterus of rabbits to induce endometritis in rabbits. Anatomical examination, blood routine examination and histopathological examination were performed on the rabbits. Rabbit uterus was collected, quantitative polymerase chain reaction (qPCR) was used to detect the mRNA expression of inflammatory factors IL-1β, IL-6, TNF-α in the rabbit uterus; enzyme-linked immunosorbent assay (ELISA) was used to detect the uterus The concentrations of inflammatory factors IL-1β, IL-6 and TNF-α were detected; Western Blot was used to detect the protein expressions of NF-kB, IKB-α and TNF-α in the NF-kB pathway. An antibiotic treatment group was also set up to verify the accuracy of the results. The results of clinical examination showed that the leukocytes in the blood of the rabbits in the model group increased significantly (P<0.01). The uterus was congested, enlarged and pus. The integrity of the uterine lining was destroyed, and the lymphocytes in the uterus increased significantly (P<0.01). The results of qPCR and ELISA showed that the expressions of inflammatory factors IL-1β, IL-6 and TNF-α in the uterus of rabbits were significantly increased (P＜0.01). Western Blot results showed that inflammatory factors IL-1β, IL-6 and TNF-α play a role in promoting inflammation through the NF-kB pathway. The results of the test provide a simple, economical and reliable means for studying the occurrence, development, prevention and treatment of equine endometritis.